(untitled) (Bangladesh Journal of Child Health, 2024)
Fibrocalculous pancreatic diabetes (FCPD) is atypical but unique variety of diabetes, in which chronic inflammation and pancreatic calcification lead to exocrine and endocrine failure of the pancreas, primarily occurs in tropical countries. At an early age, these diabetic children are at risk of developing disabling and life-threatening complications, putting a major human and economic burden on families and societies. Here, authors report a case of young female patient presenting with the clinical features of FCPD. BANGLADESH J CHILD HEALTH 2022; VOL 46 (2) : 89-91